Advancing climate resilient development pathways since the IPCC’s fifth assessment report - Werners, Saskia E; Sparkes, Edward; Totin, Edmond; Abel, Nick; Bhadwal, Suruchi; Butler, James R.A.; Douxchamps, Sabine; James, Harrhy; Methner, Nadine; Siebeneck, Jana; Stringer, Lindsay C.; Vincent, Katharine; et al. (Elsevier, 2021)
Development processes and action on climate change are closely interlinked. This is recognised by the Intergovernmental Panel on Climate Change (IPCC) in its fifth assessment report, which reports on climate-resilient pathways, understood as development trajectories towards sustainable development which include adaptation and mitigation. The upcoming sixth assessment report dedicates a chapter to climate resilient development pathways. In this context, this paper asks what conceptual and empirical advances on climate resilient development pathways were made since the fifth assessment report. Through a literature review, this paper analyses goals and approaches for climate resilient development pathways, and discusses what conceptual advances have and could still be made. We find little evidence of dedicated concept development. Rather, we observe conceptual ambiguity. Literature showed four non-exclusive clusters of approaches: (a) climate action oriented, (b) social-learning and co-creation oriented, (c) mainstreaming oriented and (d) transformation oriented. We recommend operationalising climate resilient development pathways as the process of consolidating climate action and development decisions towards long-term sustainable development. This process requires explicit engagement with aspirations of actors, and connecting past developments with future aspirations and understandings of risk. Working with multiple pathways allows us to embed flexibility, anticipation and learning in planning. A greater focus is needed on issues linked to justice and equity as climate resilient development pathways will inevitably involve trade-offs. Substantiating the concept of climate resilient development pathways has the potential to bridge climate and development perspectives, which may otherwise remain separated in development and climate policy, practice and science.